Identification of variants in GBP1 and GBP5 Genes associated with susceptibility and resistance to porcine reproductive and respiratory syndrome in Uruguayan Creole pigs - María del Carmen Montenegro; Nariné Balemian; Bibiana Freire; Cecilia Carballo; Silvia Llambí (Revista Científica, 2024)
Porcine reproductive and respiratory syndrome (PRRS) is a viral disease that affects pigs, causing significant economic losses in the global swine industry due to reproductive and respiratory problems. The causative agent of PRRS is the PRRS virus (PRRSV), primarily transmitted through direct or indirect contact via respiratory or oral routes. Despite biosecurity measures, monitoring, and vaccination, there is currently no fully effective vaccine against this virus. Research has identified a quantitative trait locus on chromosome 4 associated with PRRSV resistance. This locus includes genetic polymorphisms rs80800372 (WUR) and rs340943904 in the GBP1 and GBP5 genes, respectively. PRRSV has been detected in South America, including Uruguay in 2017. In Uruguay, the Pampa Rocha pig is the only breed of Creole pigs and is at risk due to its small population. In this context, the objective was assessing genetic variability in the Pampa Rocha breed for relevant variables related to PRRS resistance. The study determined the genotype for these variants using the end–point PCR technique, followed by Sanger sequencing. In the study, corresponding alleles were identified for each variable of interest, with allele frequencies of 0.825 for the A allele and 0.175 for the G allele in rs80800372 (WUR), and 0.825 for the G allele and 0.175 for the T allele in rs340943904. The variants are in Hardy Weinberg equilibrium and there is a linkage disequilibrium between them. The study highlights an increase in the frequency of favorable alleles related to PRRSV resistance in Pampa Rocha creole pigs. These findings underscore the importance of using molecular markers to identify PRRS–resistant animals, which could be beneficial for both pig production and animal welfare.